2007
DOI: 10.1080/01626620.2007.10463436
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Candidates' Changing Perceptions of Urban Schools: Results of a 4-Year Study

Abstract: This study investigated changes in teacher candidates' perceptions of teaching in urban schools as they completed a 4-year teacher education program. Candidates were asked to respond in writing to two questions: "What are your concerns about teaching in an urban school?" and "What are the advantages of teaching in an urban school?" Data were collected before and after a freshmen-level tutoring experience in an urban school and at the conclusion of a yearlong internship in an urban school. Participation in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…In recent reviews, however, Anderson and Stillman (2013) and Hill, Friedland, and Phelps (2012) reported that the vast majority of studies on field experiences in urban schools or community agencies focus on changes in stereotypical attitudes toward children living in poverty or increased self-efficacy in teaching in urban settings rather than teacher retention (Adams et al, 2005; Andrews, 2009; Bleicher, 2011; Coffey, 2010; Conaway, Browning, & Purdum-Cassidy, 2007; Cone, 2009; Connor, 2010; Fry & McKinney, 1997; Wiggins, Follo, & Eberly, 2007). For example, Conaway et al (2007) found that stereotypical thinking and lowered expectations for urban students changed considerably during a 4-year program as a result of diverse field experiences. Andrews (2009) found that in two sections of a multicultural education course, tutoring in an urban community organization made pre-service teachers more motivated to teach in urban schools.…”
Section: Literature On Urban Teachers’ Prior Experiences and Commitmentmentioning
confidence: 99%
“…In recent reviews, however, Anderson and Stillman (2013) and Hill, Friedland, and Phelps (2012) reported that the vast majority of studies on field experiences in urban schools or community agencies focus on changes in stereotypical attitudes toward children living in poverty or increased self-efficacy in teaching in urban settings rather than teacher retention (Adams et al, 2005; Andrews, 2009; Bleicher, 2011; Coffey, 2010; Conaway, Browning, & Purdum-Cassidy, 2007; Cone, 2009; Connor, 2010; Fry & McKinney, 1997; Wiggins, Follo, & Eberly, 2007). For example, Conaway et al (2007) found that stereotypical thinking and lowered expectations for urban students changed considerably during a 4-year program as a result of diverse field experiences. Andrews (2009) found that in two sections of a multicultural education course, tutoring in an urban community organization made pre-service teachers more motivated to teach in urban schools.…”
Section: Literature On Urban Teachers’ Prior Experiences and Commitmentmentioning
confidence: 99%
“…Many researchers have explored ways in which teacher education programs can foster positive change in attitudes and beliefs toward cultural diversity, specifically through fieldbased experiences and university coursework (Castro, 2010;Bell, Horn, & Roxas, 2007;Conway, Browning, & Purdum-Cassidy, 2007;Causey, Thomas, & Armento, 2000). The results of this study have shown urban field experiences combined with coursework and guided discussions will have positive effects on pre-service teacher's attitudes and beliefs towards culturally diverse urban schools.…”
Section: Discussion and Recommendationsmentioning
confidence: 85%
“…Extended experiences allow students to learn enough about a context to see past generalizations and stereotypical representations and to begin to develop bicultural competencies and multicultural frames of reference (Conaway et al, 2007;Stachowski & Mahan, 1998). Finally, extended experiences provide those involved with the opportunity to develop significant, respectful, and caring relationships (Bondy & Davis, 2000;Cruz, 1997;DePalma, Santos Rego, & Moledo, 2006).…”
Section: Multicultural Teacher Education Apprenticeshipsmentioning
confidence: 99%